Academic engagement in university students in the Peruvian Amazon during the post-pandemic context - Estrada Araoz, Edwin Gustavo (2023)
Introduction: Academic commitment is a construct that manifests itself through the connection of students to academic activities, which are considered as a positive challenge. Objective: To analyze the academic commitment of students from 3 universities in the Peruvian Amazon during the post-pandemic context. Method: The approach was quantitative; the design was non-experimental and the type was descriptive transectional. Academic engagement was assessed in 354 students by applying the UWES-S Scale, an instrument with adequate levels of content validity and reliability. Results: It was found that 39.3% of the students presented moderate levels of academic engagement and it was determined that this variable was significantly associated with gender, university of origin and study modality of the participants. Discussion: It is necessary for universities to promote the cognitive, affective and attitudinal domains of students to improve their academic engagement.